Cognitive Processes on Reading Literacy in Elementary Schools - Muzaki, Ferril; Dawud (Anufa Ikaprobsi, 2023)
One of the main benefits of reading is improving children's language skills. By reading books and a variety of subject matter, children will become familiar with a wider vocabulary and be able to understand different contexts. They will also learn how to write properly and effectively. The cognitive processes involved in reading literacy in elementary schools are a key factor in the development of good reading skills. This cognitive process includes basic abilities such as visual perception, word recognition, understanding phrases and sentences, as well as drawing conclusions and inferences from texts. Therefore, understanding the cognitive processes involved in reading literacy in elementary school is very important to help students acquire good reading skills and be successful in the future. This literature review study discusses cognitive processes in reading literacy in elementary schools. The purpose of this research is to understand how cognitive processes contribute to reading skills in elementary schools. The results of the study show that cognitive processes such as perception, information processing, and text comprehension are very important in helping children develop good reading skills. In addition, factors such as motivation, self-confidence, and learning strategies also have a significant influence on reading skills.